Rescaling education policy: central‐local relations and the politics of scale in England and Sweden. (1st October 2020) - Naumann, Ingela K.; Crouch, Colin
Abstract : Governments worldwide have sought to introduce greater choice and competition as mechanisms to improve the quality of education provision and outcomes. However, there is considerable cross-national variation in education policy, particularly regarding the role of local government. To explain such differences, this article focuses on recent reforms in compulsory education in England and Sweden. It shows that although governments in both countries have advocated choice, competition and participation, education reform has led to the centralisation of school governance in England but decentralisation in Sweden. Drawing on the concept of 'scalecraft' as a specific form of 'statecraft', it argues that these differences in the rescaling of education policy reflect different conceptions of central‐local relations and the role of local government. More broadly, the article shows how national governments strategically use scalar reorganisation (scalecraft) to support broader political goals (statecraft), contributing to a better understanding of the spatial dimensions of public policy reform.